Frekuensi Kebutuhan Perawatan Ortodontik Berdasarkan Index of Orthodontic Treatment Need di SMP Negeri 1 Salatiga - Perwira, Hafiizh Nur; , drg. Ana Riolina, MPH; , drg. Nilasary Rochmanita S, MDSc (2015)
Orthodontics are some of actions taken to change the occlusion in the early stages of growth, to improve oral health, oral function, and personal appearance. One the reference index in orthodontic treatment is Index of Orthodontic Treatment Need (IOTN). IOTN is a scoring system for malocclusion, developed by Brook & Shaw (1989). IOTN is used for determining the severity or degree of occlusion properties (overjet, reverse overjet, cross bite anterior/ posterior, displacement contact point, open bite anterior/posterior, and overbite). This index consists of two components: Dental health Component (DHC) and Aesthetic Component (AC). The aim of this studywas to determine frequency level of orthodontic treatment need by index of orthodontic treatment need in state junior high school 1 Salatiga. This was descriptive observational study. 84 students of state junior high school 1 Salatiga were registered as the sample. Teeth sample were constructed and the anterior picture that parallel with the occlusion were taken. The results were measured and classified according to DHC grade. The images of the teeth were analyzed by interviewing the sample according to AC grade. The results showed that frequency distribution rate of orthodontic treatment need of state junior high school 1 Salatiga students based on IOTN with DHC index was 39,3% or 33 students from total sample in state junior high school 1 Salatiga indicated that orthodontic treatment was urgently required, while AC index showed 56% or 47 students from total sample in state junior high school 1 Salatiga indicated that orthodontic treatment was unnecessary.